Scientific potential of Russian women: The past and the present - Egorychev, Aleksandr M.; Akhtyan, Anna G.; Bykov, Anatoly K.; Rychikhina, Elina N.; Lvova, Svetlana V.; Zotova, Marina V. (Linguistics and Culture Review, 2021)
Based on historical analysis of the scientific literature, the paper demonstrates the role, importance, and necessity of developing the female scientific potential in the Russian state and society. The sphere of young students’ scientific interests has been identified and substantiated with gender consideration. Similarly, possibilities of optimizing the potential of young students have been found with gender-specific aspects borne in mind. In the research, the authors used theoretical and empirical methods of collecting information about the scientific potential of Russian women. An entire range of problems (causes) has been found which prevent the potential of Russian women from being completely fulfilled in science. Principal conditions and mechanisms have been examined which help optimize the development of the scientific potential of young higher educational institution students with gender consideration. The obtained conclusions highlight the necessity of optimizing the female potential in the country’s scientific activity in the most diverse focus areas.